FLUID INCLUSIONS IN MINERALS FROM MODERN SULFIDE EDIFICES: PHYSICOCHEMICAL CONDITIONS OF FORMATION AND EVOLUTION OF FLUIDS - Bortnikov N.S.; Simonov V.A.; Bogdanov Yu.A. (My University, 2004)
A study of fluid inclusions in minerals (anhydrite, barite, and opal) from modern seafloor sulfide edifices located on the slow-spreading Mid-Atlantic Ridge (the Logachev-I, Rainbow, and Broken Spur hydrothermal fields) and in the Manus (Vienna Wood) and Woodlark basins in the southwestern Pacific was carried out. Fluid inclusions of 5-25 μm in size are two-phase at room temperature and contain liquid and a vapor bubble. Only anhydrite from the Logachev-I hydrothermal field contains three-phase fluid inclusions (liquid, a vapor bubble, and solid) and vapor-rich fluid inclusions. It was found that dissolved NaCl prevails in fluids trapped in the inclusions, while KCl is a minor constituent. Variations in the salt concentration in trapped fluids were revealed and found to lie within the following ranges (in wt % NaCl-equiv.): 4.2-26 in the fluids circulated in the Logachev-I hydrothermal system; 4.1-8.5 in the Rainbow field, 3.0-6.3 in the Broken Spur field, 1.6-7.6 in the Vienna Wood field, and 2.7-6.9 in the system within the Woodlark basin. Homogenization temperatures of fluid inclusions varied from 102 to 398°C. It was shown that the range of mineral formation temperatures and fluid salinity estimated from thermometric measurements of fluid inclusions is much wider than that obtained by direct measurements for fluids venting onto the seafloor. Variations of fluid salinity were assumed to be caused by fluid separation at a temperature near or above the critical temperature of seawater, which leads to brine formation in modern hydrothermal systems.